Avaliação econômica de sistemas fotovoltaicos conectados à rede para empreendimentos do agronegócio - Nascimento, Mario Elias Carvalho do (2019)
This investigation had as objective a comparative analysis study between the simple and discounted paybacks, which were calculated using the sizing of the studied photovoltaic systems. The work was carried out with data from three grain storage enterprises (small, medium and large) and a complex with three different aviaries of agribusiness in the western region of the state of Paraná, in Brazil. Data was collected from companies on the cost of monthly electricity consumption and monthly output. With the collected data and the global solar radiation data from the enterprises’ location, photovoltaic systems were designed to meet the demand, and the costs related to photovoltaic systems were determined, considering the costs of modules, inverters, ground support, cabling, maintenance, and inverters substitution after 10 and 20 years. Civil engineering projects were disregarded. With data on energy, production and photovoltaic systems, the simple and discounted paybacks, NPV, TIR and TIRM were calculated and the indices relating electric energy costs and the photovoltaic system costs for each enterprise were calculated. The simple and discounted paybacks of the aviary complex were of 8 and 13 years respectively; in the small grain storage companies: 7 and 11 years, medium-sized: 7 and 9 years, and large-sized: 6 and 7 years. It was also concluded with this work that all projects of photovoltaic systems were economically viable, since they presented a simple payback and a discounted payback much lower than the useful life of the project. This work was carried out with the support of the Coordination for the Improvement of Higher Education Personnel (CAPES) - Financing Code 001.